Effect of Planting Time on Canopy Structure and Biomass Production in Some Soybean Genotypes - Uddin, MK; Hasan, MK; Alam, AKMA (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A field experiment was conducted in the Field Laboratory of the Department of Crop Botany, BAU, Mymensingh during November 2003 to May 2004 to assess the effect of planting time (November and December) on some morphological structure, and root & shoot biomass production in four soybean genotypes (GPB-1, GPB-2, AGS-332 and AGS-11-35). The plant height, stem base diameter, seed dry weight plant-1 were significantly greater in the late planting crops (December) but number of branches plant-1, number of leaves plant-1, leaves dry weight plant-1, shoots dry weight plant-1, roots dry weight plant-1, total dry matter plant-1 were also significantly greater in November planting. Highest plant height, branches plant-1 and leaves plant-1, shoot dry weight plant-1 and total dry matter were found in GPB-2 genotype. Key words: Early and late planting, shoot and root mass, Glycine max. DOI = 10.3329/jard.v5i1.1453 J Agric Rural Dev 5(1&2), 25-29, June 2007